Coastal Dwellers Challenge Climate Change Through Corporate Social Responsibility Program PERMADANI BUNGUS - Viola D. Oceanio; Fakri Fakri; Ridha Djasrizal (PT. Publikasiku Academic Solution, 2025)
Climate change poses severe risks to coastal ecosystems and communities, requiring adaptive strategies that combine environmental and socioeconomic dimensions. This article explores how the PERMADANI BUNGUS program is a model of climate change adaptation through on of a Corporate Social Responsibility (CSR) initiative by Pertamina Patra Niaga Integrated Terminal Teluk Kabung. The collaboration with Teluk Buo communities such as Pokdarwis, Pokdakan, and Poklahsar integrates two core strategies to challenge climate change in coastal areas. Along with mangroves as a nature-based climate solution and economic diversification to reduce livelihood vulnerability. Mangroves are vital for climate protection and coastal resilience because of their function as carbon sequesters and coastline stabilizers. Adaptive economic initiatives such as ecotourism, floating fish cages, and fish-processed products provide alternative income for the coastal dwellers. By combining environmental rehabilitation and community empowerment can enhance coastal dwellers' resilience and sustainability in endangered coastal areas. Findings suggest that CSR can be a tool for addressing environmental risks and socioeconomic instability when it engages local communities and environmental awareness.